ONLINE PEER SUPPORT IN CYBERBULLYING: INVESTIGATING ONLINE FORA OF YOUTH HELPLINE ORGANISATIONS - Bastiaensens, Sara; Vandebosch, Heidi; Poels, Karolien; Van Cleemput, Katrien; DeSmet, Ann; De Bourdeaudhuij, Ilse (AoIR Selected Papers of Internet Research, 2015)
As cyberbullying victims can perceive various barriers for seeking social support in their face-to-face network (e.g. Baas, de Jong, & Drossaert, 2013; Hoff & Mitchell, 2009; Jacobs, Goossens, Dehue, Völlink, & Lechner, 2015), they can go online to seek for social support (Walther & Boyd, 2002), for instance in online support groups (White & Dorman, 2001). In this ‘netnographic’ (Kozinets, 2002) study, we investigated online fora discussions about cyberbullying within two online support group fora of youth helpline organizations, examining patterns of social support according to the social support framework by Tardy (1985). This framework not only helps distinguish between different types of social support (House, 1981 in Tardy, 1985), it also takes into account reciprocal support seeking and providing in a network, evaluations of social support in terms of helpfulness, and comparisons of social support sought or provided with the realm of available social support (Tardy, 1985).